Business Education for Plastic Surgeons: A Systematic Review, Development, and Implementation of a Business Principles Curriculum in a Residency Program. Issue 5 (May 2017) - Zarrabi, Bahar; Burce, Karen K.; Seal, Stella M.; Lifchez, Scott D.; Redett, Richard J.; Frick, Kevin D.; Dorafshar, Amir H.; Cooney, Carisa M.
Abstract : Background: Rising health care costs, decreasing reimbursement rates, and changes in American health care are forcing physicians to become increasingly business-minded. Both academic and private plastic surgeons can benefit from being educated in business principles. The authors conducted a systematic review to identify existing business curricula and integrated a business principles curriculum into residency training. Methods: The authors anonymously surveyed their department regarding perceived importance of business principles and performed a systematic literature review from 1993 to 2013 using PubMed and Embase to identify residency training programs that had designed/implemented business curricula. Subsequently, the authors implemented a formal, quarterly business curriculum. Results: Thirty-two of 36 physicians (88.9 percent; 76.6 percent response rate) stated business principles are either "pretty important" or "very important" to being a doctor. Only 36 percent of faculty and 41 percent of trainees had previous business instruction. The authors identified 434 articles in the systematic review: 29 documented formal business curricula. Twelve topics were addressed, with practice management/administration ( n = 22) and systems-based practice ( n = 6) being the most common. Four articles were from surgical specialties: otolaryngology ( n = 1), general surgery ( n = 2), and combined general surgery/plastic surgery ( n = 1). Teaching formats included lectures and self-directed learning modules; outcomes and participant satisfaction were reported inconsistently. From August of 2013 to June of 2015, the authors held eight business principles sessions. Postsession surveys demonstrated moderately to extremely satisfied responses in 75 percent or more of resident/fellow respondents ( n = 13; response rate, 48.1 percent) and faculty ( n = 9; response rate, 45.0 percent). Conclusions: Business principles can be integrated into residency training programs. Having speakers familiar with the physician audience and a session coordinator is vital to program success. Abstract : Supplemental Digital Content is available in the text.